The power of sale promotions: Analyzing the impact of sales promotion offerings on consumer buying behavior in the pandemic - Huseynzade, Sadi (Zielona Góra: Faculty of Economics and Management Press)
The present research aimed to explore the impact of sales promotions on consumer behavior during the COVID-19 pandemic. The study analyzed consumer reactions to various promotion types such as bonuses, coupons, buy one get one free, vouchers, free samples, and price discounts. The aim was to investigate if these promotions positively influence consumer purchasing behavior and if the pandemic has induced overpurchasing behavior due to panic.
Keywords: sales promotions; consumer buying behavior; pandemic